Academic Resilience: Understanding Family Relationships That Promote it - Salvo-Garrido, Sonia Ilse (2021)
The study of academic resilience is relevant to the educational environment because of its positive role in the educational and socio-emotional development of children and adolescents. The objective of the article was to understand the family relationships that favor academic resilience in elementary school students, first to fourth year, from vulnerable contexts. The methodology used to respond to the objectives considered a grounded theory design, since it sought to describe and understand the meanings constructed intersubjectively by the participants. The participants were selected through a guided theoretical sampling, in which data collection and analysis were carried out in parallel, with the main theoretical guide being the emerging theoretical model. The data collection strategy considered the application of 27 semi-structured interviews to vulnerable families, for which a thematic guide was prepared containing the main topics to be addressed with the participants, and without a standard scheme of response categories. Data analysis protocols and procedures were based on coding paradigm and included open, axial and selective coding levels. The results suggest that family relationships based on communication, trust, and strict academic standards combined with parental emotional support, favor academic resilience. Likewise, high academic expectations and school commitment, characterized by a component of parents affection towards school, contribute to promoting academic resilience. Finally, results are discussed from national and international theoretical evidence available, highlighting those healthy family relationships that promote academic resilience.